Effect of Korean Medicine Treatments for Fat Pad Syndrome of Knee Joint: A Case Report - June-Haeng Lee; Soo-Kyung Lee; Eun-Yeong Park; Sun-Woo Kang; Yoon-Jae Won; Jae-Joon Ha; Myeong-yeol Yang (MEDrang Inc., 2022)
Fat pad syndrome is a knee joint condition/disease where acute or chronic inflammation occurs in the fat pad of the knee joint, and it is a cause of anterior knee pain. Fat pad syndrome usually occurs concurrently with other conditions/diseases to collectively cause anterior knee pain. No study to date has reported the treatment of anterior knee pain solely due to fat pad syndrome. Here, we report a case of fat pad syndrome of the knee joint as the sole cause of anterior knee pain in a 49-year-old woman who received integrated Korean medicine treatments (pharmacopuncture, acupuncture, herbal medicine, deep fascial meridian therapy, and chuna). Using patient-reported pain scale scores, the level of the patient's pain was relieved, and her mobility improved. Integrated Korean medicine treatments could be effective for patients who have fat pad syndrome of the knee joint.